Effects of energy and protein supplementation on microbial-N synthesis and allantoin excretion in sheep fed guinea grass - Jetana, T; Abdullah, N; Halim, R.A; Jalaludin, S; Ho, Y.W (Elsevier, 2000)
An experiment was conducted to determine the effects of two types of protein, soybean meal (SBM) and fish meal (FM); and two types of energy supplements, corn flour (CF) and paper pulp (PP) on in vivo digestibility of organic matter (OM), rumen fermentation pattern and dilution rate, rumen microbial-N synthesis and flow of organic matter and nitrogenous compounds through the duodenum in four Merino rams with an average weight of 54.4±4.5 kg. The relationships between duodenal purine flow and urinary allantoin and duodenal protein/energy (MJ rumen VFA per day) ratio were also investigated. The experiment was conducted in a 4 x 4 Latin square design with a 2 x 2 factorial arrangement of dietary treatments. The animals, fitted with both rumen and duodenal cannulae were housed in individual crates and fed chopped fresh guinea grass ad libitum twice daily, 100 g molasses and one of the four dietary supplements: (i) 170 g FM+268 g PP (FM+PP); (ii) 170 g FM+268 g CF (FM+CF); (iii) 200 g SBM+200 g PP (SBM+PP); and (iv) 200 g SBM+200 g CF (SBM+CF). Each supplement, at varying rates of rumen degradability, was formulated to provide similar amount of N and gross energy. The results showed that rumen pHs were similar, ranging from pH 5.8 to 6.0, for all animals fed the different dietary supplements. Rumen ammonia concentration was significantly (p<0.05) higher in animals fed SBM (170.2-190.7 mg N1-1) than in animals fed FM supplement (166.8-170.2 mg N l-1). Rumen VFA concentrations were similar (94-103 mM) but molar proportions of acetate and propionate were respectively lower and higher in treatment SBM+CF, leading to a significantly decreased acetate:propionate ratio in this treatment (3.6) compared to SBM+PP (4.3). There were no significant differences between treatments in rumen fluid dilution rate and rumen volume. Duodenal OM flow was similar in PP supplemented diets, but differed significantly (p<0.05) between protein supplements in the CF diets. Organic matter digestibility in the rumen was significantly (p<0.05) higher in the CF+FM diet. Moreover, animals fed SBM supplement showed higher total tract OM digestibility than animals fed FM supplement. The flow of nitrogenous compounds to the duodenum, i.e., total-N, non-ammonia-N and rumen-undegradable-N were not significantly affected by either protein or energy supplements. Microbial-N flow tended (p<0.08) to be higher in sheep fed CF supplement (average of 10.2 g per day) than in those fed PP supplement (average of 8.1 g per day). Urinary allantoin excretion was low (0.30-0.42 mmol per day/kg BW0.75). A positive linear correlation (r=0.73, p<0.005) between urinary allantoin (μmol per day/kg BW0.75) and duodenal purines (μmol per day/kg BW0.75) was observed. The efficiency of rumen microbial-N synthesis based on OM truly digested in the rumen was significantly (p<0.02) higher in sheep fed CF supplement (15.2-16.6 g N kg-1 OMTDR) than in those fed PP supplement (12.2-12.8 g N kg-1 OMTDR). Differences in microbial protein:energy ratio or total duodenal protein:energy ratio among dietary treatments were not significant.